2018
DOI: 10.1111/ene.13645
|View full text |Cite
|
Sign up to set email alerts
|

Demand for neurological services in Central Eastern Europe: a 10‐year national survey in Hungary

Abstract: The demand for neurological services is high in Hungary; close to 30% of the population used an inpatient or outpatient neurological service at least once during this 10-year period. Results from this project provide data for international comparisons and help to ensure better informed and more focused resource allocation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
0
7
0
1
Order By: Relevance
“…The details of NEUROHUN database have been published elsewhere [19]. Briefly, we used data submitted to the NHIF by healthcare providers with contract, including all public hospitals, contracted private hospitals, and outpatient specialist services, between 1st January 2004 and 31st December 2016.…”
Section: Setting Of Databasementioning
confidence: 99%
“…The details of NEUROHUN database have been published elsewhere [19]. Briefly, we used data submitted to the NHIF by healthcare providers with contract, including all public hospitals, contracted private hospitals, and outpatient specialist services, between 1st January 2004 and 31st December 2016.…”
Section: Setting Of Databasementioning
confidence: 99%
“…As we found a considerable difference between the two districts of Budapest regarding the age at the index event, we decided to further test our study hypothesis in a supplementary analysis. For this reason, we requested and accessed data of patients with ischemic stroke for all 23 districts of Budapest from an ongoing nationwide project [19] and related the mean age of the patients at the index event to the mean annual income of the respective district for all 23 districts. We have found that the higher the mean annual taxable income, the older the mean age of patients at the index ischemic stroke (Fig 4, p<0.001).…”
Section: Resultsmentioning
confidence: 99%
“…Our study was performed using the NEUROHUN 2004–2017 database, which was created from medical and medication prescription reports within the framework of the Hungarian National Brain Research Program 6 . Appearances in all in- and outpatient departments (except family medicine (FM)) in Hungary in the indicated period are documented in the database.…”
Section: Methodsmentioning
confidence: 99%